Proposta para seleção de peneiras vibratórias no sistema de tratamento de lamas em sondas de perfuração - Campos, Camila do Nascimento (Brasil, 2019)
In drilling an oil well, it is essential to use the drilling fluid, as they are responsible for the control of several factors, such as solids transport, cooling and lubrication of the drill bit in addition to the pressure balance in the well during drilling. When returning the drilling fluid needs to be treated by various equipment such as the shale shaker, hydrocyclones and centrifuges. This work proposes studies and analyzes for the selection of shale shaker in the sludge treatment system in drilling rigs, evaluating the capacity of the sieves in the process of separation of solids. The development of the proposal will be based on a study of the characteristics of the geological formations, as well as a comparative map of selection of sieves according to manufacturer's catalogs, thus allowing the identification of the parameters of greater influence in the treatment process of the sludge. The expected results are to obtain the volume of gravel and mud generated, besides the rates of production of gravel and mud during the drilling, to later evaluate the capacity and quantity of shale shaker that will best meet the volume coming from the well.